PENGARUH AUDIT INTERNAL PENGELUARAN KAS TERHADAP PENGENDALIAN INTERN PENGELUARAN KAS PADA PERUSAHAAN FASHION DI KOTA BANDUNG - S Mia Lasmaya; Jimmy Rusjiana (Jurnal Computech & Bisnis (e-Journal), 2019)
To continue to be able to manage the company's operations effectively, management must be subjected to various types of reporting and analysis. Of course, this contains risks that are caused by errors (errors) that may arise in the process of presenting multiple types of reports. Management requires control tools in the form of internal control. Control is the power to govern the financial and operational policies of an entity to benefit from the activities of that entity. The research method uses a survey approach with a sample of fashion companies in the city of Bandung. The results showed a significant influence on the internal audit of cash disbursements on the internal control of cash disbursements. Keywords : internal audit, internal control.